Respiratory diseases and mortality in non-traumatic patients exposed to the 2023 Türkiye earthquake disasters: a retrospective observational study - Ömür Güngör; Özlem Erçen Diken; Sinem Berik Safcı; Akkan Avcı; Ali İsa Aslan (BMJ Open)
Objective On 6 February 2023, two massive earthquakes occurred in Kahramanmaras province in Türkiye. In addition to direct physical damage, earthquakes can also significantly affect individuals’ respiratory health in the postdisaster period. This study aimed to investigate respiratory diseases and related mortality following earthquakes.Design This is a retrospective observational study. 1 month following the earthquake, all cases that came to the emergency department between 6 February 2023 and 6 March 2023 who required a pulmonologist consultation were included (n=278). All cases requiring a pulmonologist consultation who were admitted to the emergency department within the same date period 1 year ago (6 February 2022–6 March 2022) were included in the control group (n=255).Setting Türkiye, Adana Province.Outcome measures Respiratory diseases, mortality risks in 3 weeks and 3 months, and factors that may affect mortality were investigated in the population exposed to the earthquake.Results Pneumonia had the highest rate among admissions in the postearthquake period (36.0%). The pneumonia rate and pneumonia-related deaths were significantly higher compared with those in the previous year (OR: 2.28, 95% CI: 1.05 to 4.94 and OR: 2.49, 95% CI: 1.15 to 5.39; 3-week and 3-month mortality, respectively). The disease that had the second highest admissions rate was chronic obstructive pulmonary disease exacerbation (25.9%). Earthquake exposure is associated with increased risk of 3-week (OR: 1.58, 95% CI: 1.03 to 2.43) and 3-month mortality (OR: 1.55, 95% CI: 1.03 to 2.36).Conclusions The period after the earthquake is associated with an increase in the incidence of pneumonia and a poor prognosis for patients with pneumonia. Considering all cases, earthquake exposure has a negative impact on the prognosis of respiratory diseases.